Technologischer Wandel und Ungleichheit - Stella Zilian; Maximilian Unger; Wolfgang Polt; Wilfried Altzinger (Wirtschaft und Gesellschaft (WuG), 2016)
The on-going digitalization of economic activities has once again fuelled the discussion concerning the effects of technological change on employment and the income distribution. This article investigates recent empirical studies and, despite the methodological and conceptual differences that are found, identifies several key findings. In the medium run productivity gains seem to be neutral with regard to employment, although significant negative effects may occur in the short run. In addition, these effects might vary among sectors. The effects of innovation intensity also differ among sectors and firms where product innovations in particular seem to have positive effects on employment. Any displacement induced by technological change affects workers differently depending on their tasks and qualifications. This leads to a polarization at the labour market. The unequal impact of technological change on different occupations in turn partly determines the income distribution, which also exhibits a tendency towards polarization. At the same time, aspects of market structure and market power are relevant for the distribution of income among firms as well as between firms and employees. This article therefore concludes that the distributional issues in connection with technological change have to be discussed in a new perspective considering the varying impact of technological change on the income distribution between people with different qualifications as well as between capital and labour.
Keywords: 330; Technischer Fortschritt; Soziale Ungleichheit